PROLONGED QT AND MONOMORPHIC VT: A RARE PRESENTATION OF PHEOCHROMOCYTOMA - Aziz, Hazwani; Kamaruddin, Muhammad Hilmi; Paramasivam, Sharmila; Ibrahim, Luqman; Lim, Lee-Ling; Vethakkan, Shireene; Loch, Alexander; Ratnasingam, Jeyakantha (Journal of the ASEAN Federation of Endocrine Societies, 2021)
INTRODUCTION Pheochromocytomas classically present with the triad of headaches, palpitations and diaphoresis; and very rarely with isolated cardiac rhythm abnormality. RESULTS We report a 46-year-old female with pheochromocytoma presenting with prolonged QT interval and monomorphic ventricular tachycardia (VT). She has no known cardiovascular risk factors. She initially presented at the emergency room with chest tightness and palpitations. Her BP was 200/100 mmHg and she was tachycardic (110 beats/ min). ECG showed widespread deep T wave inversion with significantly prolonged QTc, 580 milliseconds. Troponin I levels were elevated and she was treated for acute coronary syndrome. Within an hour of presentation, she developed multiple episodes of monomorphic VT requiring amiodarone infusion. Echocardiography revealed preserved left ventricular ejection fraction (55%) with hypokinetic apical, lateral and anterior left ventricular wall. Further history revealed loss of weight of 6kg and paroxysms of cold sweats over the past 3 months. The 24-hour urinary catecholamines and metanephrines were elevated more than 30x the upper limit of normal. Imaging showed a 4.8 x 4.5 x 5.5 cm mass in the right adrenal gland. A diagnosis of right adrenal pheochromocytoma was made. She was commenced on alpha-blockade with phenoxybenzamine, followed by cardio-selective betablockade with bisoprolol. After two weeks of adequate blockade and volume expansion, she underwent right adrenalectomy. Postoperatively, she required no antihypertensives and had no recurrence of VT. Her ECG showed resolution of T wave inversions and significantly improved QTc, at 495 milliseconds. Upon follow-up 2 months post-operatively, she remained normotensive with no arrhythmias and normalised urinary catecholamines and metanephrines. CONCLUSION The toxic effects of catecholamines include coronary vasospasms, cardiomyopathy and diverse electrocardiographic abnormalities of rhythm, conduction and repolarization, which can manifest as acute coronary syndrome, heart failure or prolonged QT intervals and malignant arrhythmias. This case provides a vignette for this rare presentation and resolution of these cardiac abnormalities with treatment of pheochromocytoma.